Present Status and Challenges on Agricultural Microbe Bio-Prospecting in Indonesia - Sukara, Endang (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2007)
food security is one of the essential needs which can never be ignored by any society, including in particular Indonesia. as the world population is expected to rise to around 10 billion marked by 2025. The problem is that the agriculture in developed and developing countries that follow the path of developed countries experiences create · a range of serious environmental degradation. An intensive agricultural production through the use of pesticide and herbicides, forest clearing and continued use of land resources for the agricultural purposes are not sustainable practice . In consequences, degradation of ecosystem, oil erosion. and low productivity of land, poor water quality and lost of biological diversity (including microbial and genetic resources) occurred at alarming stale. Meanwhile, the efforts in addressing the above situation is traditionally focused on plant phenotypes (breeding. plant genetic engineering etc .) but the important role of microbial communities that interact with plants to influence plant health and productivity has been largely ignored. The interaction of microbes with plants and its relevant to soil fertility and productivity, the bio-control properties of microbes and challenges toward sustainable agriculture is highlighted.